2015
DOI: 10.1108/intr-11-2013-0247
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of e-shopping: an integrated model

Abstract: Purpose -The purpose of this paper is to present an integrated information systems-consumer behavior (IS-CB) model for e-shopping to examine the antecedents and consequences of e-shopping and usage behavior. Design/methodology/approach -The study tests 320 usable responses collected from e-shoppers against the integrated model using structural equation modeling. Findings -The main research results support the use of antecedents of e-shopping acceptance and usage by drawing from unified knowledge of IS and CB u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 129 publications
2
86
0
2
Order By: Relevance
“…Ha and Stoel, 2009;Lim, 2015a;Lim and Ting, 2012). In that sense, the model is likely to suffer from overwhelming replication, with the possibility that endeavours to offer incremental contributions to the field may become extremely difficult, if not nearly impossible-an issue that resonates with many in the information systems and technology discipline (Lim, 2016).…”
Section: Revisiting Tammentioning
confidence: 99%
“…Ha and Stoel, 2009;Lim, 2015a;Lim and Ting, 2012). In that sense, the model is likely to suffer from overwhelming replication, with the possibility that endeavours to offer incremental contributions to the field may become extremely difficult, if not nearly impossible-an issue that resonates with many in the information systems and technology discipline (Lim, 2016).…”
Section: Revisiting Tammentioning
confidence: 99%
“…As IS research has shown, delays in online transactions can be perceived as a flaw that may ultimately have a negative impact on continuation to use the website (Everard & McCoy 2010). In a similar vein, any features that irritate customers during the interaction with a website (e.g., interruptions) deteriorate the customer experience and hence, have a negative impact on attitude and usage intention (Lim 2014). To summarize, partial transaction support will result in positive customer experiences due to higher customer engagement and interaction, but may also be less appreciated by customers due to delays of transaction completion.…”
Section: Australasian Journal Of Information Systems Madlberger and Matmentioning
confidence: 99%
“…Indeed, e-commerce business models can differ substantially in their effect on sales generation because important factors such as price reductions or dynamics in sales processes can look very differently (Wang et al 2016). Considering this rich body of work, it comes as a surprise that e-commerce business models are described as the most discussed yet least understood concepts in the ecommerce field (Veit et al 2014 The value provided by an e-commerce business model is decisive for customers' choice of the e-commerce channel (Lim 2014) and, as a further consequence, also for the reuse intention (Adapa & Cooksey 2013;Wang et al 2016). Nowadays e-commerce business models are often based on multiple channels, also referred to as bricks and clicks business models (Herhausen et al 2015).…”
Section: E-commerce Business Modelsmentioning
confidence: 99%
“…Instead, noteworthy efforts are being made to extend (e.g. through theoretical integration; Lim, 2015) or apply (e.g. in experimental settings; Teh et al, in press) the technology acceptance model meaningfully.…”
Section: Reviewmentioning
confidence: 99%